Measurement of the Tensor-Analyzing Power Component T20 for Incoherent Negative Pion Photoproduction on a Deuteron; Atoms; Vol. 11, iss. 6 - Kuzmenko A. S. Anna Sergeevna; Gauzshteyn (Gauzshtein) V. V. Vyacheslav Valerjevich; Darwish E. M.; Fiks (Fix) A. I. Alexander Ivanovich; Kuzin M. Ya. Matvey Yaroslavovich; Levchuk M. I.; Loginov A. Yu. Aleksey Yurjevich; Nikolenko D. M. Dmitry Mitrofanovich; Rachek I. A. Igor Anatoljevich; Shestakov Yu. V. Yury Vladimirovich; Toporkov D. K. Dmitry Konstantinovich; Yurchenko A. V. Arseny Vladislavovich; et al. (2023, 2023)
Title screen